Developmental Links between the Fetal and Adult Zones of the Adrenal Cortex Revealed by Lineage Tracing - Zubair, Mohamad (American Society for Microbiology (ASM), 2008)
The nuclear receptor Ad4BP/SF-1 is essential for development of the adrenal cortex and the gonads, which derive from a common adrenogonadal primordium. The adrenal cortex subsequently forms morphologically distinct compartments: the inner (fetal) and outer (definitive or adult) zones. Despite considerable effort, the mechanisms that mediate the differential development of the adrenal and gonadal primordia and the fetal and adult adrenal cortices remain incompletely understood. We previously identified a fetal adrenal-specific enhancer (FAdE) in the Ad4BP/SF-1 locus that directs transgene expression to the fetal adrenal cortex and demonstrated that this enhancer is autoregulated by Ad4BP/SF-1. We now combine the FAdE with the Cre/loxP system to trace cell lineages in which the FAdE was active at some stage in development. These lineage-tracing studies establish definitively that the adult cortex derives from precursor cells in the fetal cortex in which the FAdE was activated before the organization into two distinct zones. The potential of these fetal adrenocortical cells to enter the pathway that eventuates in cells of the adult cortex disappeared by embryonic day 14.5. Thus, these studies demonstrate a direct link between the fetal and adult cortices involving a transition that must occur before a specific stage of development.